The Development of an Innovative Leadership Program for Nursing Administrators at Community Hospitals Under the Ministry of Public Health - Rodphothong, Jidapa; Meksuwan, Wattanasom; Koohathongsumrit, Nitidetch; Sanarmthong, Ekkasit (Journal of Bamrasnaradura Infectious Diseases Institute, 2026)
This study utilized Research and Development. The researcher examines (1) the components of the innovative leadership of the nursing administrators; develops, (2) an innovative leadership program, and (3) the constructed program. The researcher conducted three steps as follows. 1) Studied the components of innovative leadership. The population consisted of 550 nursing administrators at community hospitals using the technique of multi-stage sampling. The research instrument was a questionnaire. The experts checked the content validity and the item objective congruence (IOC). The statistics used in the data analysis were percentage. The technique of exploratory factor analysis (EFA) was also employed. 2) Developed a program checking. The technique of focus group discussion was conducted with nursing administrators to confirm the program, and 3) Implemented and evaluated the constructed program. The sample population was purposively selected consisting of nursing administrators at the community hospitals in Nonthaburi province. The research instruments consisted of an observation form and a knowledge test. The statistics used were frequency and percentage. The technique of the paired samples t test was also employed. Findings are as follows: 1. Innovative leadership of nursing administrators in community hospitals comprised: (1) providing the creation of an innovative development environment; (2) fostering creativity and having a vision for change; having creative communication; (4) having systematic thinking and efficient decision-making; and (5) having a growth mindset. 2. The program development with the concept of design thinking and outcome-based education, with experts checking the program structure found to exhibit consonance and the suitability of the program at the highest level. The focus group discussion found the implementation of the program to be appropriate. The curriculum was developed based on Design Thinking and Outcome-Based Education (OBE). Expert validation confirmed its consistency and highest level of appropriateness. Focus group results confirmed its practical feasibility for implementation. 3. The program experiment showed the following. (1) The average score of knowledge after the experiment with the program was at a higher level than prior to the experiment at the statistically significant level of .05. (2) The aspect of the program effectiveness was found to exhibit overall suitability at the highest level ( ) = 4.66).